Long noncoding RNA SchLAH suppresses metastasis of hepatocellular carcinoma through interacting with fused in sarcoma. Issue 4 (17th April 2017) - Ge, Zhouhong; Cheng, Zhuoan; Yang, Xinrong; Huo, Xisong; Wang, Ning; Wang, Hui; Wang, Cun; Gu, Dishui; Zhao, Fangyu; Yao, Ming; Fan, Jia; Qin, Wenxin
Abstract : Emerging evidence has indicated that deregulation of long non‐coding RNAs (lncRNAs) can contribute to the progression and metastasis of human cancer, including hepatocellular carcinoma (HCC). However, the roles of most lncRNAs in HCC remain largely unknown. Here we found a long noncoding RNA termed SchLAH (seven chromosome locus associated with HCC; also called BC035072) was generally downregulated in HCC. Low expression of SchLAH was significantly correlated with shorter overall survival of HCC patients. In vitro and in vivo assays indicated that overexpression of SchLAH inhibited the migration and lung metastasis of HCC cells. Knockdown of SchLAH by siRNA pool promoted the migration of HCC cells. RNA pull‐down and RNA immunoprecipitation assays demonstrated SchLAH physically interacted with fused in sarcoma (FUS). PCR array analysis showed that RhoA and Rac1 were the downstream effector molecules of SchLAH during HCC metastasis. Knockdown of FUS rescued the mRNA levels of RhoA and Rac1 that were repressed by SchLAH . These results suggest that SchLAH may suppress the metastasis of HCC cells by interacting with FUS, which indicates potential of SchLAH for the prognosis and treatment of HCC. Abstract : Our results showed that SchLAH was down regulated in HCC. SchLAH may suppress the metastasis of HCC cells by interacting with FUS, which indicates potential of SchLAH for the prognosis and treatment of HCC.